Вивчення безпечності екстракту з трави люцерни посівної = Safety study of extract of medicago sativa sowing grass - Yeriomenko, Rimma F.; Maloshtan, Lyudmila N. (Journal of Education, Health and Sport, 2015)
Yeriomenko R F, Maloshtan L N. Вивчення безпечності екстракту з трави люцерни посівної = Safety study of extract of medicago sativa sowing grass. Journal of Education, Health and Sport. 2015;5(2):23-32. ISSN 2391-8306. DOI: 10.5281/zenodo.14896 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A23-32 https://pbn.nauka.gov.pl/works/534392 http://dx.doi.org/10.5281/zenodo.14896 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. УДК: 615.32:582.736.3:001 ВИВЧЕННЯ БЕЗПЕЧНОСТІ ЕКСТРАКТУ З ТРАВИ ЛЮЦЕРНИ ПОСІВНОЇ SAFETY STUDY OF EXTRACT OF MEDICAGO SATIVA SOWING GRASS Р.Ф.Єрьоменко, Л.М.Малоштан RF Yeriomenko, LN Maloshtan Національний фармацевтичний університет (м. Харків, Україна) Department of Physiology and Anatomy of the National University of Pharmacy, Kharkiv, Ukraine nedtrans2@rambler.ru Резюме В даній роботі установлено відсутність токсичної дії після одноразового внутрішньошлункового введення щурам-самцям та щурам-самкам ЕТЛП в дозі 5000 мг/кг. Згідно з загальноприйнятою токсикологічною класифікацією речовин ЕТЛП при внутрішньошлунковому введенні належить до V класу токсичності – практично нешкідливих речовин (ЛД50 >5000 мг/кг). Результати макро- та мікроскопічних досліджень внутрішніх органів через 14 днів після одноразового внутрішньошлункового введення ЕТЛП у дозі 5000 мг/кг показали відсутність будь-яких анатомічних та морфологічних порушень у тканинних структурах щурів самців та самок. Розраховане значення ТІ, яке лежить за межами 200, свідчить про високий ступінь безпечності ЕТЛП та його перспективність для медичної практики як ефективного та безпечного коректора білкового обміну з анаболічною дією. Ключові слова: безпечність, екстракт з трави люцерни посівної, гостра токсичність, доза ЛД50, морфоструктура тканин. Abstrakt In this study there was determined the absence of toxic effect after a single intragastric administration of EGMS at a dose of 5000 mg / kg to male and female rats. According to the conventional toxicological classification of substances, under the intragastric administration EGMS belongs to class V of toxicity – practically harmless substances (LD50 >5000 mg / kg). The results of macro- and microscopic studies of internal organs in 14 days after a single intragastric administration of EGMS at a dose of 5000 mg / kg showed the absence of any anatomical and morphological disorders in tissue structures of male and female rats. The calculated value of TI, which lies beyond 200, indicates a high level of safety of EGMS and its prospectivity for medical practice as an effective and safe corrector of protein metabolism with an anabolic action. Key words: safety, an extract from the herb alfalfa seed, acute toxicity, LD50 dose, morphological structure of tissues.